A Comprehensive in silico Analysis of mt-CO1 gene of Fasciola hepatica - Celik, Figen; Simsek, Sami; Kesik, Harun Kaya; Gunyakti Kilinc, Seyma (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was conducted for the aim of comprehensive evaluation of the genetic diversity and phylogenetic relations of F. hepatica among various hosts. In this study, published sequences of mt-CO1 gene fragments belonging to final hosts of F. hepatica were used to create the dataset. First of all, 478 sequences were obtained with PubMed search. Then, some shorter sequences were removed after alignment, and 319 sequences which included cattle (n=242), sheep (n=46), goat (n=5), donkey (n=8), bison (n=7), water buffalo (n=7), human (n=2) and camel (n=2) sequences were analysed in the MEGA X program. The existence of 72 haplotype groups was detected. The most polymorphic sites (n=42) containing 31% (13/42) parsimony informative sites were detected in Iranian isolates. The mt-CO1 network consisted of 35 haplotypes, 80% out of which were geographically unique. However, a main haplotype consisting of 39.2% of the total isolates was formed. The bison isolates of F. hepatica showed the highest haplotype diversity within the final host isolates, followed by the sheep, water buffalo, cattle, goat and donkey isolates. The genetic diversity of F. hepatica in different hosts and countries revealed the possibility of new strains appearing in the future.